Network analysis of the associations between personality traits, cognitive functioning, and inflammatory markers in elderly individuals without dementia - Bastelica, Thomas; Lespine, Louis-Ferdinand; Rouch, Isabelle; Tadri, Myriam; Dorey, Jean-Michel; Strippoli, Marie-Pierre F.; d'Amato, Thierry; von Gunten, Armin; Preisig, Martin; Rey, Romain (Frontiers in Aging Neuroscience, 2023)
Age-related cognitive decline has been associated with personality traits and systemic inflammatory markers. Further associations have been found between personality traits and inflammatory markers. However, no study to date explored relationships between personality traits, inflammatory markers, and cognitive performance altogether. The present study aimed to better understand the inter-relationships among these variables in healthy elderly people using a network analysis approach, a statistical method that allows visualizing the unique pairwise associations that are present in the data. We performed a cross-sectional analysis on 739 healthy elderly individuals, using data from Colaus|PsyColaus, a population-based study conducted in Lausanne, Switzerland. Personality traits were assessed with the Revised NEO Five-Factor Inventory (NEO-FFI-R) and interleukin (IL)-1β, IL-6, Tumor Necrosis Factor-α (TNF-α) and C-reactive protein (CRP) were used as peripheral inflammatory markers. Cognitive domains were investigated using Mini-Mental State Examination (MMSE), Verbal fluency, Stroop, DO40, and the Double Memory Test. In healthy elderly individuals, Openness was associated with Verbal fluency, and Agreeableness with immediate Free Recall. In contrast, no association between inflammatory markers and personality traits or cognition were identified. A high level of Openness or Agreeableness may be a protective factor against age-related cognitive decline, in executive functioning or memory, respectively.